An autopsy case of GM1 gangliosidosis type II in a patient who survived a long duration with artificial respiratory support. Issue 4 (27th March 2020) - Uchino, Akiko; Nagai, Makiko; Kanazawa, Naomi; Ichinoe, Masaaki; Yanagisawa, Nobuyuki; Adachi, Kaori; Nanba, Eiji; Ishiura, Hiroyuki; Mitsui, Jun; Tsuji, Shoji; Suzuki, Kinuko; Murayama, Shigeo; et al.
Abstract : GM1 gangliosidosis is a storage disorder with autosomal recessive inheritance caused by deficiency of β‐galactosidase (GLB1), which is a lysosomal hydrolase, due to mutations in GLB1 . We describe here an autopsy case of GM1 gangliosidosis in a female patient who survived for 38 years with a long period of artificial respiratory support (ARS). She was born after a normal pregnancy and delivery. Although development was normal until one year old, she was unable to walk at two years old and started having seizures by nine years old. At 21 years old, she became unable to communicate and was bed‐ridden. At 36 years old, she suffered from pneumonia and required ARS. She died of pneumonia at 40 years old. Neuropathological examination revealed severe atrophy, predominantly found in the frontal lobes. Microscopically, severe gliosis and neuronal loss were observed in the cerebral cortex, putamen, cerebellum, the latter including Purkinje cell and granule cell layers. The hippocampus was relatively preserved. Severe neuronal swelling was observed in the limbic regions and stored a material in these neurons negative for periodic acid‐Schiff (PAS). A PAS‐positive granular storage material in neurons and macrophages was mainly observed in the brainstem and limbic regions. Exome analysis showed a known c.152T>C (p.I51T) variant that has been described in type III patients and a novel c.1348‐2A>G variant in GLB1 . Detailed analysis of reverse transcription‐polymerase chain reaction products of GLB1 mRNA revealed that these variants were present in a compound heterozygous state. In our case, clinical features and neuropathological findings were most consistent with type II, although the entire course was longer than any previously reported cases. This may be explained by the residual enzyme activity in this patient whose severity lay between types II and III. Our finding of relative preservation of the limbic regions suggests that neuronal loss in GM1 gangliosidosis has regional selectivity.